Women’s control over income: Implications for women’s empowerment and the agricultural sector - Njuki, Jemimah; Boote, Sophie; Doss, Cheryl (International Food Policy Research Institute, 2019)
Across Africa, rural transformation is taking place, and agriculture remains a central driver of that transformation. Agricultural production is the most important sector in most African countries, averaging 24 percent of gross domestic product (GDP) for the region. Agribusiness supplies, processing, marketing, and retailing add about 20 percent of GDP (O’Sullivan et al. 2014). Urbanization and rapidly changing consumption patterns have fueled a sharp shift in diets beyond grains into nongrain foods, such as dairy, fish, meat, vegetables, fruit, and tubers, and heavily into processed foods. In any scenario, agriculture will continue to play a greater role than has been the case in other transformations around the world. Although the development literature contains analyses of rural agricultural transformation and what it means for youth, the gender dimensions are lacking. It is critical to ensure that women receive and control an equitable share of the benefits of the rural transformation processes that are occurring in various forms and at various speeds throughout Africa.